PENGARUH PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN KANGKUNG (Ipomoea reptans Poir.) DAN IKAN LELE (Clarias gariepinus) SECARA AKUAPONIK SERTA SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Maratul Aripah; Rahmi Susanti (Bio-Lectura : Jurnal Pendidikan Biologi, 2022)
The research aims to determine the effect of chicken manure fertilize on the growth of Kale plant (Ipomoea reptans Poir.) and catfish (Clarias gariepinus) with aquaponic. The research employed a completely randomized design consisting of five treatments and five replications. The treatments consisted of P0 (0 g/l), P1 (0,25 g/l), P2 (0,50 g/l), P3 (0,75 g/l) and P4 (1 g/l). The data of the research were analyzed using the ANOVA test and advanced tests with Least Significant Difference (LSD). The results showed that the dose of chicken manure as much as 0.25 g/l (P1) gave the best results for the growth of water spinach and sangkuriang catfish. The average wet weight of shoots and roots of kale was 178.13 g and 32.69 g, respectively, while the dry weight of the shoots was 8.99 g, and the dry weight of the roots was 1.99 g. As for an average fish weight growth rate 105,82 grams and an average total length of fish 5,87 cm. Based on the results of the study, it can be concluded that chicken manure fertilizer gives a real effect on the growth of kale and catfish which is kept with aquaponic technique. The results of this research can be utilized on biology learning in class XII on basic competencies 3.1 and 4.1 about growth and development of living things that are donated in the form of teaching material in the form of student worksheets.